The contribution of a hermeneutic approach to investigate psychological variables in second language acquisition - Chang, Qing (Frontiers in Psychology, 2022)
Qualitative research and more specifically a hermeneutic approach to interpreting communications in L2 classes has much to contribute to the accumulation of psychological knowledge about L2 learners. The modern social hermeneutic approach helps to address questions that are quite relevant for explaining contemporary developments in L2 educational strategies and policy-making. It can be used alone or in combination with quantitative methods of data analysis to analyze how certain psychological variables (cognitive factors, affective factors, and personality traits) emerge from the social interactions that occur within the ecologically situated nature of classroom language learning. Though the hermeneutic approach has been effectively used in other disciplines such as clinical psychology, industrial psychology and organizational management to accumulate psychological knowledge, there are hopes that it can be used in L2 studies to explore the emergence, development, and causal mechanisms underlying the psychological variables in the interactive context of L2 classes. These will have contributions to L2 psychology, educational psychology, and second language acquisition (SLA) domains.